Introduction to protein structure - Brändén, Carl-Ivar, 1934- (Garland Pub., 1991)
Illustrates (in clear color diagrams) and explains for both biologists and chemists the structural and functional logic that has emerged from the latest accumulated data on protein structures *** Karolinska Institute, Stockholm, Sweden. Textbook on the atomic structures of proteins. For students. Includes colorful illustrations.